Kemampuan Literasi Sains Mahasiswa PGSD Universitas PGRI Adi Buana Surabaya - JUNIARSO, TRIMAN (Fakultas Bahasa dan Sains, Universitas Wijaya Kusuma Surabaya, 2019)
Science literacy is a person's ability to understand science so that it is able to apply (Dani, 2009). Students who have scientific literacy skills can either apply their knowledge to solve problems in everyday life both in private, social or global (OECD, 2009). This study aims to describe the scientific literacy skills of PGSD students, the first semester of the University of PGRI Adi Buana Surabaya. Science literacy tests are adapted from PISA 2012 questions and consulted with experts. Students are given 50 minutes to solve the test questions given. Student answers were then analyzed and described based on nominal, functional, procedural, and multidimensional categories. From the results of the analysis it was found that the scientific literacy skills of the first semester PGSD students were in the nominal category (41.25%), functional categories (38.42%), procedural categories (21.18%), and the remainder in the multidimensional category.